A single case study on the effect of raktamokshan with jaluka in the adhimantha vyadhi with special reference to chronic simple glaucoma- a case study: SINGLE CASE STUDY - dhanvijay, sukeshini (Ayurline: International Journal of Research in Indian Medicine, 2023)
ABSTRACT- Introduction- Glaucoma is one of the serious condition causing parmanent blindness if it is not properly and promptly treated in the initial stage. It is characterised by raised intraocular pressure, field defects and optic atrophy leading to gross visual loss. Intraocular pressure is the most common risk factor but not only risk factor for development of glaucoma. Some of the clinical features of Adhimantha can be corelated with glaucomaÂ Glaucoma is counted under the sarvagata rogas described by Acharya Sushruta. Â Adhimantha has been occured to negligience or improper management of abhishyanda both from diagnostic as well as treatment point of view. Material and Methods- A 55 year old male patient came to Shalakyatantra OPD in Chhatisgarh Ayurvedic College Rajnandgaon with chief complaints of headache , nausea, vomitting ,pain in eyes, visual defect and blurring of vision since 1 month. He was treated with Raktamokshan with Jaluka in 4 sittings in one month ( once in a week). Result- At the end of study means after one month improvement in the maintaing the intraocular pressureÂ reduce the symptoms like headache , pain in eye, nausea and vomitting. Conclusion- Thus it can be concluded that Raktamokshan with jaluka are helpful to control glaucoma.